2001
DOI: 10.1080/00224540109600549
|View full text |Cite
|
Sign up to set email alerts
|

Social Traditionalism and Economic Conservatism: Two Conservative Political Ideologies in the United States

Abstract: The authors surveyed by telephone a random sample of voters in the 1996 presidential election from the Standard Metropolitan Statistical Area of Muncie, IN ("Middletown"; R. Lynd & H. Lynd, 1929) to test a model describing the nature of 2 conservative political ideologies--social traditionalism and economic conservatism. The model, based on functions of attitudes theory, predicted (a) that the 2 political ideologies would appeal to 2 rather distinct constituency groups--the former, to conservative Protestants;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 20 publications
3
54
0
Order By: Relevance
“…We found that, pooled across nations, high NSC predicted conservative position on cultural attitudes, as well as right-wing self-identification, but that it slightly predicted left-wing economic attitudes. This pattern is consistent with the findings of several previous studies that have examined NSC's separate relations with sociocultural and economic attitudes (e.g., Feldman & Johnston, 2014;Johnson & Tamney, 2001;Johnston, 2013). Thus, far from underlying a broad-based conservative ideology, NSC predicted a configuration of attitudes that is socioculturally right wing but that leans to the left in the economic domain.…”
Section: Nsc's Menu-independent Influence On Left-wing Economic Attitsupporting
confidence: 91%
“…We found that, pooled across nations, high NSC predicted conservative position on cultural attitudes, as well as right-wing self-identification, but that it slightly predicted left-wing economic attitudes. This pattern is consistent with the findings of several previous studies that have examined NSC's separate relations with sociocultural and economic attitudes (e.g., Feldman & Johnston, 2014;Johnson & Tamney, 2001;Johnston, 2013). Thus, far from underlying a broad-based conservative ideology, NSC predicted a configuration of attitudes that is socioculturally right wing but that leans to the left in the economic domain.…”
Section: Nsc's Menu-independent Influence On Left-wing Economic Attitsupporting
confidence: 91%
“…More specifically, in Experiment 3 participants were asked to complete the very same task presented in Experiment 2 and their need for closure and need for cognition were also assessed. Moreover, in Experiment 3 the measure of political ideology comprised items related to both social and economic issues [28], [29]. We predicted that, as demonstrated in Experiment 2, conservatives, as compared to liberals, would be more likely attracted by negative stimuli, and would thus be faster to detect a probe appearing in the same spatial location of such negative stimuli, even when other specific individual differences (i.e., need for closure and need for cognition) are taken under control.…”
Section: Resultsmentioning
confidence: 99%
“…Research on the psychological correlates of economic conservatism has been much more sporadic than that associated with cultural conservatism, RWA, and SDO. However, the evidence that does exist suggests that economic conservatism relates positively with need for closure (Kossowska and Van Hiel 2003)-again in Western samples-and negatively (though not significantly) with dogmatism (Johnson and Tamney 2001;Ray 1973). Moreover, measures of economic conservatism have been shown to correlate positively with SDO (Cornelis and Van Hiel 2006;.…”
Section: Economic Conservatism and Disability-related Attitudesmentioning
confidence: 86%